Peran Linguistik Forensik pada Era Perkembangan Teknologi Komunikasi - Hendrokumoro Hendrokumoro; Moh. Masrukhi; Lin Shofwata D.; I Desak Ketut Titis Ary Laksanti (Faculty of Cultural Sciences, 2019)
The introduction of forensic linguistics to government agencies engaged in law is a community service activity carried out by the Linguistic Masters Study Program, Faculty of Cultural Sciences, Universitas Gadjah Mada on July 18, 2019. This activity was conducted at Wonogiri Regional Police Station and was attended by participants from the Wonogiri District Police, the Wonogiri District Court, and the Wonogiri District Prosecutor's Office. The introduction of forensic linguistics was dilivered through a presentation of previous studies relating to forensic linguistic problems. As technology develops, language problems in society also develop. The next stage is a joint discussion about problems experienced by the participants in their activities related to forensic linguistic problems. The community service aims to realize the goal of the government in educating public on social media.————————————————————-Pengenalan linguistik forensik kepada badan pemerintah yang bergerak di bidang hukum merupakan salah satu bentuk kegiatan pengabdian masyarakat yang dilakukan oleh Program Studi Magister Linguistik, Fakultas Ilmu Budaya, Universitas Gadjah Mada pada 18 Juli 2019. Kegiatan ini dilakukan di Polres Wonogiri dan dihadiri oleh peserta dari Polres Wonogiri, Pengadilan Negeri Wonogiri, dan Kejaksaan Negeri Wonogiri. Pengenalan linguistik forensik dilakukan dengan tahap presentasi kajian terdahulu yang berkaitan dengan masalah lingustik forensik. Oleh karena teknologi semakin berkembang, maka masalah-masalah kebahasaan yang ada dalam masyarakat pun turut berkembang. Tahapan selanjutnya adalah diskusi bersama tentang persoalan-persoalan yang dialami oleh para peserta kegiatan terkait dengan masalah linguistik forensik. Kegiatan ini bertujuan mewujudkan cita-cita pemerintah untuk mencerdaskan masyarakat dalam bermedia sosial.